Alleviating Chilling Injury in Stored Pomegranate Using a Single Intermittent Warming Cycle: Fatty Acid and Polyamine Modifications - Leila Taghipour (Hindawi Limited, 2021)
Pomegranate is a perishable superfruit with important human health-promoting phytochemicals. The use of cold storage is inevitable for its long-term preservation. As pomegranate is sensitive to temperatures below 5°C, it is therefore necessary and worthwhile to introduce a postharvest technique that is safe, applicable, and commercially acceptable to maintain the fruit quality under a cold storage condition. The efficacy of intermittent warming (IW) in the form of a single warming period (1 day at 20°C with 70% relative humidity (RH) before returning the treated fruit to storage) during the cold storage of ‘Rabab-e-Neyriz’ pomegranate (70 days at 2 ± 0.5°C and 90 ± 5% RH) was evaluated. To find the best treatment time, warming was performed at 4 temporary interruption points in storage (after 15, 25, 35, or 45 days of storage). For each interruption date, the treated fruit were compared to the controls twice, once immediately after treatment and once at the end of the storage period. It was founded that a single warming period at the right time during cold storage (before irreversible damage occurs) activated multiple mechanisms and physiological responses in pomegranate fruit peel that are significantly responsible for alleviating the severity of chilling damage to this commodity. In other words, warming on the 15th day was the most efficient treatment, resulting in better preservation of unsaturated fatty acids from peroxidation, lower malondialdehyde (MDA) production, and preservation of the unsaturated/saturated fatty acids (UFAs/SFAs) ratio (membrane integrity index) in the peel during storage and lower chilling injury symptoms. Moreover, the content of spermine (Spm) and putrescine (Put) (as important antioxidants acting as membrane safety agents) was significantly increased immediately after treatment, followed by a continuous increase in Spm and a higher level of Put compared to control until the end of storage.